PENGARUH STRUKTUR MODAL DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN PADA INDUSTRI MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI - Binti Kurniasih; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to analyze the factors that affect the capital structure and investment decisions on the value of the company. The population in this research is all food and beverage industries listed in Indonesia Stock Exchange which amounted to 15 companies with period 2012-2014. The data measurement technique in this research use the ratio of DER, PER and PBV, result of data analysis or regression result stated that capital structure have negative effect to capital structure, investment decision have positive effect to firm value and simultaneously capital structure and investment decision have significant effect to firm value . Keywords : Capital Structure, Investment Decisions, Firm Value